The impact of early childhood bereavement - Bowman, Sarah Nicole (Kansas State University, 2023)
This report investigates the psychological effects of bereavement on young children aged three to five years. It will discuss how these effects can be minimized and how we can help children grieve a loss with support in their environments including within the home and in the classroom. Personal experiences, stories, and interviews from parents who have experienced the loss of a child will be shared. The information from research will be combined with personal experiences to create a brochure entitled Siblings Grieve Too, which can be used as a meaningful vehicle to inform the public about early childhood bereavement. The research paper and brochure will give details that can help inform caregivers and support our grieving children specifically geared towards children ages three to five years. Experiencing the death of a sibling during childhood and early adulthood is a common phenomenon, affecting between 5% and 8% of children with one or more siblings in the United States. Research has shown that children who experience bereavement at a young age are at an increased risk of developing a range of psychological issues, including depression, anxiety, and post-traumatic stress disorder. The child’s environment and support systems decrease the severity and longevity of these risks. Facilitating an open, honest communicative approach with grieving children is a huge benefit for children, it will foster verbalizations of feelings, and understanding of the situation revolving death, in which will help the child achieve successful grievance and return to their psychological baseline. Grief can lead to short term changes during the immediate and initial stages but through environmental support can return to baseline, we see that the environment provides a foundation for successful or dysfunctional grievance. Children, no matter how young they are, do feel the absence of a loved one. The influence of families on their young children shows the affect they have on their successful coping, or struggle, with death.
Keywords: Psychological effects of bereavement on young children